CRISPR/Cas genome editing system and its application in potato - Hou, Xin; Guo, Xiaomeng; Zhang, Yan; Zhang, Qiang (Frontiers in Genetics, 2023)
Potato is the largest non-cereal food crop worldwide and is a vital substitute for cereal crop considering its high yield and great nutritive value, playing an important role in food-security. CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated) system has the advantages of easy operation, high efficiency and low cost, which shown the potential in potato breeding. In this paper, the action mechanism and derivative types of CRISPR/Cas system are summarized and its application in breeding and the development of novel commercial traits of potato are reviewed.